Basic Financial Recording Training for Batik Pringmas MSMEs in Banyumas Regency - Kurnia Indah Sumunar; Chusnul Maulidina Hidayat; Muhammad Eka Purbaya; Joseph Alfred M Reyroso (SWAGATI : Journal of Community Service, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting local economic growth and preserving regional cultural heritage. One of the MSMEs with significant cultural and economic potential is KUB Batik Pringmas in Banyumas Regency. However, the business group still faces challenges in financial management, especially in preparing systematic financial records and financial statements. This community service activity aimed to improve the participants’ understanding of basic financial recording and financial management. The activity was conducted through observation, lectures, discussions, and question-and-answer sessions. The training involved 20 batik artisans from KUB Batik Pringmas. The materials included basic accounting equations, financial statement components, cash flow management, and basic bookkeeping practices. The results showed that participants gained improved knowledge of basic financial management, improved skill to make basic financial statement, and improved motivation to record the transaction, with the average evaluation score increasing from 64.0% in the pretest to 83.6% in the posttest. Participants also demonstrated high enthusiasm during the activity despite language barriers because the material was delivered bilingually in Indonesian and English. Overall, the program contributed positively to improving financial literacy and strengthening financial management awareness among Batik Pringmas MSMEs.